A Novel Oncogenic Driver in a Lung Adenocarcinoma Patient Harboring an EGFR-KDD and Response to Afatinib - Chen, Dong; Li, Xing-liang; Wu, Biao; Zheng, Xiao-bin; Wang, Wen-xian; Chen, Hua-fei; Dong, Yi-yu; Xu, Chun-wei; Fang, Mei-yu (Frontiers in Oncology, 2020)
Introduction Oncogenic mutations in the epidermal growth factor receptor (EGFR) are found in a subset of patients with non-small cell lung cancer (NSCLC) and serve as important predictive biomarkers in this disease. EGFR exon 18-25 kinase domain duplication (EGFR-KDD) mutations recently emerged as a new EGFR gene molecular subtype in non-small cell lung cancer (NSCLC) is extremely rare. Case presentation Herein, we reported a rare case of a 59-year-old male diagnosed with adenocarcinoma. A biopsy revealed an EGFR-KDD identified by the next generation sequencing (NGS). The patient had a favorable tumor response to afatinib, a tyrosine kinase inhibitor. Conclusion This case highlights that adjusting our strategy and using newly available tools, such as comprehensive NGS tests, could prove useful in detecting alternative ways in which the EGFR pathway is altered in tumors.